A qualitative account of young people's experiences of alcohol screening and brief interventions in schools: SIPS Jr-HIGH trial findings. (21st August 2019) - Giles, E L; McGeechan, G J; Scott, S J; McGovern, R; Boniface, S; Ramsay, A; Hendrie, N; McColl, E; Sumnall, H; Newbury-Birch, D; Kaner, E; ,
Abstract: Background: The United Kingdom (UK) has seen a decrease in the number of young people drinking alcohol. However, the UK prevalence of underage drinking still ranks amongst the highest in Western Europe. Whilst there is a wealth of evidence reporting on the effectiveness of both primary, and secondary interventions, there are few reports of the experiences of young people who receive them. Methods: The present study reports findings from interviews with 33 young people who were involved in an alcohol screening and brief intervention randomized controlled trial in schools in England. All interviews were analysed using inductive applied thematic analysis. Results: Three major themes were identified following the analysis process: 1) drinking identities and awareness of risk; 2) access to support and advice in relation to alcohol use; and 3) appraisal of the intervention and potential impact on alcohol use. Conclusions: There appeared to be a reluctance from participants to describe themselves as someone who drinks alcohol. Furthermore, those who did drink alcohol often did so with parental permission. There was variation amongst participants as to how comfortable they felt talking about alcohol issues with school staff. Overall participants felt the intervention was useful, but would be better suited to 'heavier' drinkers.